2001
DOI: 10.1046/j.1440-1665.2001.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

New Roles for Old: The Role of The Psychiatrist in The Interdisciplinary Team

Abstract: Objectives:The contributions of the psychiatrist to the interdisciplinary team are described, along with the opportunities for, and barriers to, effective teamwork. Conclusions:Australasian health and medical training systems still provide perverse incentives deterring psychiatrists from becoming full members of interdisciplinary teams. Sources of potential role conflict should be resolved, and advantages of teamwork support, division of labour, crossfertilisation and hybrid vigour should be realised. Truly es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…In particular, this group reported collegial nurse‐doctor relationships at a higher level (3.13) than reported for magnet hospitals in the United States (Lake, 2002; Lake & Friese, 2006), and higher than other Australian general nursing research (Middleton et al, 2008). This is indicative of strong interdisciplinary relationships and may be a consequence of the nature of work in mental health settings, described as inherently multidisciplinary (Grigg, 2001; Rosen, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this group reported collegial nurse‐doctor relationships at a higher level (3.13) than reported for magnet hospitals in the United States (Lake, 2002; Lake & Friese, 2006), and higher than other Australian general nursing research (Middleton et al, 2008). This is indicative of strong interdisciplinary relationships and may be a consequence of the nature of work in mental health settings, described as inherently multidisciplinary (Grigg, 2001; Rosen, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown how the CF, when used to collect information about a clinical case and then as an outline for a clinical case conference, allows participants to move from an emphasis on biomedical diagnostic issues -in which the psychiatrist plays the pre-eminent role (Rosen 2001) -toward a broader interdisciplinary exchange, which is open to solutions from participants from multiple disciplines. The CF framework fostered this interdisciplinarity in several ways:…”
Section: Resultsmentioning
confidence: 99%
“…a dominant professional culture overwhelming a recovery-based approach)? 80 Do such safeguards also promote a positive experience for both service users and care-givers 95 and their participation in decision-making, both at management and clinical levels? 96…”
Section: Hierarchymentioning
confidence: 99%
“…While no profession has a monopoly on 'comprehensive' training, assessment or intervention, 80 each team member brings to the team an in-depth knowledge of, and advanced competence in, a particular model of mental health care that needs to be maintained by continuing professional development. 24 Informed by annual one-to-one appraisals, each professional line manager can collaboratively formulate a professional development plan that identifies the training needs of same-discipline team members.…”
Section: Profession-specific Needsmentioning
confidence: 99%